1992
DOI: 10.1007/bf01703064
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence of a variant of coxsackievirus A24, an agent causing acute hemorrhagic conjunctivitis

Abstract: The complete nucleotide sequence was determined for the cDNAs that represent the RNA genome of the standard strain of a variant of coxsackievirus A24, the EH24/70, one of the agents causing acute hemorrhagic conjunctivitis. The genome is 7461 nucleotide long and is polyadenylated at the 3'-end terminus. Following a 750-nucleotide 5'-noncoding region, there was a long open reading frame of 6642 nucleotides, which serve to encode a viral polyprotein consisting of 2214 amino acids. Comparison of the deduced amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…There is no experimental evidence that recombinants between PV and NPEV are viable. However, there are findings suggesting that such recombinants circulate in nature, as the remarkable similarity to PV of the 3Ј end of the CA21 or the CA24 reference strains shows (15,36). Thus, it is clear that OPV-derived PVs can acquire highly modified genomes not only by mutation but also by genetic exchanges with vaccine or wild PV, or even with NPEV.…”
Section: Discussionmentioning
confidence: 99%
“…There is no experimental evidence that recombinants between PV and NPEV are viable. However, there are findings suggesting that such recombinants circulate in nature, as the remarkable similarity to PV of the 3Ј end of the CA21 or the CA24 reference strains shows (15,36). Thus, it is clear that OPV-derived PVs can acquire highly modified genomes not only by mutation but also by genetic exchanges with vaccine or wild PV, or even with NPEV.…”
Section: Discussionmentioning
confidence: 99%
“…Biotinylated nested-PCR products were sequenced using a direct solid-phase T7-polymerase-mediated nucleotide sequencing strategy, using either a fluorescein-labelled sequencing primer for analysis with an ALF automated DNA sequencer (Pharmacia) as described previously by Nicholson et al (1995), or an unlabelled sequencing primer and Dyedeoxy terminators (Applied Biosystems) for analysis with a 373 automated DNA sequencer (Applied Biosystems). Sequences thus derived were compared with published enterovirus sequences (Chang et al, 1989;Drebot et al, 1994;Hughes et al, 1989;Dahllund e~ al., 1995;Iizuka et al, 1987;Jenkins et al, 1987;Klump et al, 1990;Kraus et al, 1995;Lindberg et al, 1987;Pulli et al, 1995;P6yry et al, 1994;Romero & Rotbart, 1995;Ryan et al, 1990;Supanaranond et al, 1992;Toyoda et al, 1984;Zhang et at., 1993;Zheng et al, 1995), using DNASIS to estabish the likely serotypic identity of viruses detected by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…replacing the conventional error function (Rumelhart et al, 1986) (Ryan et al, 1990) ok (Supanaranond et al, 1992) ok (Chang et al, 1989) ok (Iizuka et al, 1987 (Robertson et al, 1985) aThe cleavage type and corrected cleavage sequence and entry name are shown, as well as position of erroneous site (Old) and corrected (New). The status of the corresponding GenBank entry is also indicated if available (plus accession number).…”
Section: The Neural Network Algorithmmentioning
confidence: 99%